Application of Earned Value Analysis Method and Earned Schedule Method to Time and Cost Control In Bank X Building Project - Achmad Rizki T. A; Niko Akbar M. W; Triana Suci R; Aryati Indah K (CV. Syntax Corporation Indonesia, 2024)
In the execution of construction projects, time and cost control is an important aspect to achieve profitability and efficiency. Delays and cost increases are common, which can be detrimental to the project. Therefore, an appropriate analysis method is needed to predict and control project performance. This study aims to analyze project performance and estimate the final time and cost of the project using the Earned Value Analysis (EVA) and Earned Schedule (ES) methods. This research uses a quantitative descriptive approach by analyzing existing data. Data were collected through surveys and observations at the research site, as well as interviews with relevant parties. The EVA method was used to evaluate project progress, while ES was used to improve the accuracy of time prediction. The results of the analysis showed that in week 28, the Cost Variance (CV) value was Rp. 1,126,276,650.65 with a Cost Performance Index (CPI) of more than 1, indicating that the work was completed at a lower cost than budget. The time performance index (SPI) of 1.003 indicates that the work was completed faster than planned. Overall, the estimated cost and time of project completion showed savings of 12.63%, which amounted to Rp. 4,380,694,868. This study concludes that the application of EVA and ES methods can effectively improve time and cost control in construction projects.